Research On The Study Of Art And Design: A Study On The Paradigmatic Philosophical Framework Towards The Field Of Visual Arts And Design Research - Mustaqim, Karna; Adiwijaya, Rio; Indrajaya, Ferdinand (2014)

(untitled)
The purpose of this paper is to briefly show the paradigm behind the idea of practice-based nature of art and design inquiries and made discussion of some fundamental aspects of art / design, in order to explain and justify its practice-based character as commensurate to research in the higher education context. It is to review recent literature that addresses various issues towards the idea of art and design as a ‘practice-based’ instead of research-based inquiry which is quite novelty. By considering the importance of the issue and but the same time its depth and complexity comprising of philosophical underpinnings, thorough this article researcher would like to discuss its ontological basis of art / design works vis a vis natural fact, followed by showing their epistemic character in comparison to scientific knowledge. This research employed an investigation of the aspects of implicit philosophical assumptions about the view of the nature of the world (ontology) of art and design, and the way to understand (epistemology) artistically and designerly paradigm of inquiry, then finally about its plausible method of art and design in conducting creative research. This study come up with a kind of proposal about re-examination, if art and design subsume themselves under commonly known as a scientific research paradigm. Art and design do not observe and predict existing facts to find a formulation on making and designing. The task of art and design is to invent and innovate creatively, by proposing new meaning and possibilities with respect to many things imaginable, instead of assuming ‘universal’ and mechanical reproducibility of any research findings. Since art and design endeavors, primarily do not concern with objective fact findings and mechanical predictions of them, but with “making sense of things”, otherwise the consequence would be counter-productive.